2015
DOI: 10.1021/jacs.5b03113
|View full text |Cite
|
Sign up to set email alerts
|

Structural Requirements for Palladium Catalyst Transfer on a Carbon–Carbon Double Bond

Abstract: Intramolecular transfer of (t)Bu3PPd(0) on a carbon-carbon double bond (C═C) was investigated by using Suzuki-Miyaura coupling reaction of dibromostilbenes with aryl boronic acid or boronic acid esters in the presence of various additives containing C═C as a model. Substituent groups at the ortho position of C═C of stilbenes are critical for selective intramolecular catalyst transfer and may serve to suppress formation of the bimolecular C═C-Pd-C═C complex that leads to intermolecular transfer of (t)Bu3PPd(0).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
41
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 21 publications
4
41
0
Order By: Relevance
“…In this context, it occurred to us that Suzuki Miyaura coupling polymerization using tetraalkoxy-substituted 4,4¤-dibromostilbene would enable such switching, because the t-Bu 3 P-ligated Pd catalyst walks from one phenyl ring to the other through the carboncarbon double bond (C=C) in model reactions, while the intramolecular catalyst transfer is suppressed by trapping the catalyst by addition of alkenes such as styrene and stilbene. 8 In this paper, we report that SuzukiMiyaura polycondensation of substituted 4,4¤-dibromostilbene 1 and substituted 4,4¤-stilbenediboronic acid ester 2 afforded highmolecular-weight poly(biphenylenevinylene) (PBPV) with boronate at both ends even when an excess of 1 was used, whereas this abnormal unstoichiometric polycondensation was altered to normal unstoichiometric polycondensation in the presence of unsubstituted stilbene as a promoter of intermolecular catalyst transfer, resulting in a decrease of the molecular weight and change of the polymer ends to bromine ( Figure 1). PBPV is a member of the poly(phenylenevinylene)s (PPVs), which have been extensively investigated for application in light-emitting diodes, and many functional groups can be introduced into the two phenylene rings of PBPV.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, it occurred to us that Suzuki Miyaura coupling polymerization using tetraalkoxy-substituted 4,4¤-dibromostilbene would enable such switching, because the t-Bu 3 P-ligated Pd catalyst walks from one phenyl ring to the other through the carboncarbon double bond (C=C) in model reactions, while the intramolecular catalyst transfer is suppressed by trapping the catalyst by addition of alkenes such as styrene and stilbene. 8 In this paper, we report that SuzukiMiyaura polycondensation of substituted 4,4¤-dibromostilbene 1 and substituted 4,4¤-stilbenediboronic acid ester 2 afforded highmolecular-weight poly(biphenylenevinylene) (PBPV) with boronate at both ends even when an excess of 1 was used, whereas this abnormal unstoichiometric polycondensation was altered to normal unstoichiometric polycondensation in the presence of unsubstituted stilbene as a promoter of intermolecular catalyst transfer, resulting in a decrease of the molecular weight and change of the polymer ends to bromine ( Figure 1). PBPV is a member of the poly(phenylenevinylene)s (PPVs), which have been extensively investigated for application in light-emitting diodes, and many functional groups can be introduced into the two phenylene rings of PBPV.…”
mentioning
confidence: 99%
“…This result indicated that dibromo monomer 1 would react successively with 2 equiv of 2 and/or an oligomer with Bpin ends through intramolecular catalyst transfer on the C=C in 1 (Figure 3), as observed in model reactions of 4,4¤-dibromostilbene, having four alkoxy groups at the same position as 1 has, with phenylboronic acid ester in the presence of tBu 3 PPd(0) catalyst. 8 The formation of Bpin chain ends even in the presence of excess dibromo monomer 1 is responsible for the occurrence of the abnormal unstoichiometric polycondensation. In the MALDI-TOF mass spectrum of the polymer obtained after 3 h (Figure 2b), Bpin/Bpin and Bpin/B(OH) 2 were major peaks, but peaks due to Bpin/H with an even number of repeat units were also observed.…”
mentioning
confidence: 99%
“…This is due to the Ni(0) catalyst remaining adhered to the polymer chain, preventing “ring‐walking” from occurring. Very stable metal π‐aryl complexes have been observed with polymerizations of thiophene‐benzothiadiazole‐thiophene, thienothiophenes, and p ‐phenylene vinylene monomers . The ligand to metal donation of the benzene amino ligand may be weaker if the aniline moiety is not donating electron density toward the phosphine group.…”
Section: Resultsmentioning
confidence: 99%
“…This is similar to the interchain catalyst transfer reported for the Pd(0) species when double bonds are present in the monomer. 24 This process results in the formation of H/Br terminated oligomers of BDP-Oct. Finally, the competitive transfer, associated to the catalyst instability, leads to no complete conversion of the GRIM monomer.…”
Section: Synthesis Of the Polymers Using External Initiatormentioning
confidence: 99%